2023
DOI: 10.1097/iae.0000000000003945
|View full text |Cite
|
Sign up to set email alerts
|

From drusen to type 3 macular neovascularization

Elodie Bousquet,
Ahmad Santina,
Giulia Corradetti
et al.

Abstract: Purpose: To investigate the imaging features preceding the occurrence of type 3 (T3) macular neovascularization (MNV) using tracked spectral-domain optical coherence tomography (SD-OCT). Method: From a cohort of eyes with T3 MNV and ≥ 12 months of prior tracked SD-OCT, T3 lesions that developed above soft drusen were selected for OCT analysis. Retinal imaging findings at the location where type T3 MNV occurred were analyzed at each follow-up until the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 18 publications
0
1
0
Order By: Relevance
“…MNV3 often develops over a large druse or a drusenoid PED [46]. In a multicenter cohort study of 31 patients with treatment-naïve MNV3, Bousquet et al [47] found a progressive increase in drusen size/PED height prior to the MNV3 development. Further, they reported a MNV3 location at the apex of the druse/drusenoid PED in 95% of cases.…”
Section: Pathophysiologymentioning
confidence: 99%
“…MNV3 often develops over a large druse or a drusenoid PED [46]. In a multicenter cohort study of 31 patients with treatment-naïve MNV3, Bousquet et al [47] found a progressive increase in drusen size/PED height prior to the MNV3 development. Further, they reported a MNV3 location at the apex of the druse/drusenoid PED in 95% of cases.…”
Section: Pathophysiologymentioning
confidence: 99%